The relationship between kindergarten teachers’ prosocial motivation and emotional support competence: the mediating role of a sense of professional mission and nonlinear moderating effect of teaching experience - Yuanyuan Lin; Zhiruo Lin; Caiping Cai; Men Wei; Fajie Huang (BMC Psychology)
Abstract Background Emotional support competence is essential for kindergarten teachers, shaping both children’s socio-emotional development and the classroom environment. Prosocial motivation, defined as the desire to benefit others, has been recognized as a key predictor of this competence, but the underlying mechanisms remain unclear. A sense of professional mission may serve as a mediator, bridging intrinsic motivation and practical skills. Furthermore, teaching experience may exert a nonlinear moderating effect, shaping how prosocial motivation translates into emotional support competence at different career stages. Aim This study explored the relationship between prosocial motivation and emotional support competence among kindergarten teachers, with a particular focus on the mediating role of a sense of professional mission and nonlinear moderating effect of teaching experience. Participants and method A questionnaire survey was conducted with 2,960 in-service kindergarten teachers from mainland China. The study controlled for the following variables: education level, professional title, and kindergarten level. After controlling for these three variables, data were analyzed using mediation and moderation models to explore the mechanisms linking prosocial motivation, emotional support competence, and professional mission, with a focus on the nonlinear effects of teaching experience. Results (1) Kindergarten teachers’ prosocial motivation was found to significantly and positively predict emotional support competence. (2) A sense of professional mission played a significant mediating role in this relationship. (3) Teaching experience exhibited a nonlinear moderating effect on the relationships among prosocial motivation, emotional support competence, and professional mission. Specifically, as teaching experience increased, the predictive power of prosocial motivation on both emotional support competence and professional mission gradually weakened. However, the facilitating effect of professional mission on emotional support competence remained stable across different levels of teaching experience. Conclusion This study reveals the mechanisms linking prosocial motivation to kindergarten teachers’ emotional support competence, emphasizing the mediating role of professional mission. It also challenges the assumption of linear career growth. The findings suggest that strategies designed to enhance teachers’ professional mission and the tailoring of interventions based on teaching experience could bolster emotional support competence in early childhood education. Further research is needed to explore these dynamics longitudinally and in diverse cultural contexts.